SOCIOPRAGMATIC STRATEGIES FOR SUNDANESE LANGUAGE PRESERVATION IN YOUTUBE VIDEOS FEATURING DEDI MULYADI - Imas Melasari; Yayat Sudaryat; Temmy Widyastuti (Universitas Islam Sumatera Utara (UISU), 2026)
The declining use of regional languages in Indonesia necessitates the search for innovative preservation strategies in the digital era. Unlike previous studies that have focused primarily on political communication and media framing, this study highlights the sociopragmatic dimensions of regional language preservation through digital communication. This study analyzes sociopragmatic communication strategies within Kang Dedi Mulyadi's YouTube content, focusing on the use of Sundanese and speech elements that enhance the vitality of regional languages. Using a descriptive qualitative approach, data from three of Kang Dedi Mulyadi's YouTube videos were transcribed and coded into relational, educational, and cultural/identity categories, and subsequently analyzed through thematic interpretation. This study substantiates the notion that the sociopragmatic practices of public figures on digital platforms can serve as a potential model for revitalizing regional languages. The findings extend sociopragmatic perspectives by demonstrating how digital discourse contributes to regional language revitalization through the integration of cultural identity, communicative practices, and audience engagement.